臺灣東南亞客家研究目錄整理 - 劉堉珊; Yu-shan Liu (My University, 2015)
本文的編輯目的在製作臺灣教學／研究機構與出版社所產出之東南亞客家研究目錄。目錄主要針對者為臺籍學者與學生，但也包含在臺灣任職、就學的外籍學者與學生。

This catalogue is a collection of articles, books and theses on Southeast Asian Hakka produced in Taiwan. It aims to give an overview of the topics and areas which Taiwan's Southeast Asian Hakka studies have taken interest in and conducted research on to date.
Catalogue of Taiwan's Southeast Asian Hakka Studies
Keywords: 東南亞; 客家; 臺灣; Southeast Asia; Hakka; Taiwan